Generalized Fermi sea for plane-wave Hartree-Fock theory. II. Semi-realistic interactions in three dimensions - Aguilera-Navarro, V. C.; Belehrad, R.; De Llano, M.; Sandel, M.; Vary, J. P.; Rojo, O. (American Physical Society (APS), 1980)
The possibility of abnormally occupying plane-wave Hartree-Fock determinants is studied analytically for several many-fermion systems interacting with short- and long-ranged pair potentials in three dimensions. Lower energy states are found in some cases, but they always depend sensitively on the shape of the potential as well as on the amount of space exchange present in the interaction. NUCLEAR STRUCTURE Plane-wave Hartree-Fock, nuclear matter. © 1980 The American Physical Society.